‘IDDAH OF DEATH DIVORCE FOR CARRER WOMAN IN PERSPECTIVE JASSER AUDA’S MAQASID SHARIA - Mas Umar (Study Program of Islamic Family Law, Syari'ah Faculty, University of Al-Hikmah Indonesia, 2023)
Islam greatly glorifies women as human beings who act as mothers and teachers for their children. In fact, not a few women in Indonesia bear the burden of family living expenses. A woman whose husband dies, she is obliged to carry out iḥdȃd. Woman in the period of 'iddah is forbidden from wearing jewelry, interacting with men who are not mahram without any intention, and she is prohibited from wearing clothes that can attract men's attention to her. Iḥdȃd as an attempt to show loyalty and protect the rights of her husband when her husband dies. Women who practice iḥdȃd are not allowed to preen, wear jewelry, silk clothing, perfume, and eye shadow. This situation will become a problem when a career woman is required to work outside the home to support her family, while she has limited time due to carrying out iḥdȃd obligations. This research emphasizes the emergency aspects for career women when leaving iḥdȃd which may have more benefit values reviewing it by the perspective of Jasser Auda's maqasid sharia. This article is a type of qualitative research with a phenomenological descriptive approach that examines the phenomenon of career women. The results of this research conclude that iḥdȃd for career women who pose a danger to work and threaten survival, then she may not carry out iḥdȃd with the condition that she still has to look after and protect herself so that marriage does not occur and things that are prohibited by Islam do not occur during the ‘iddah.